Tibrena Tourism Attraction as an Alternative Destination in Sibolangit District Deli Serdang Regency - Tambunan, Ellyta Effrida; Sipayung, Lydia De Vega (Politeknik Negeri Bandung, 2023)
The artificial tourist attraction is a tourist destination that is quite popular today, artificial tourist attraction is a man-made tourist attraction that is interesting to visit. The artificial attractions found in Tibrena Sibolangit include a floating restaurant above a fish pond, a camping ground, lodging, and a large field. Therefore, researchers are interested in knowing more about the attractiveness of tourism made by Tibrena. Like Something To Do, Something To See, Something To Buy, Something To Arrive, Something To Stay. And knowing whether Tibrena in Sibolangit can be said to be artificial tourism. This research was conducted using qualitative methods and data collection techniques used in this study were observation, interviews, questionnaires, documentation, and a combination of the four. The samples in this study were tourists and managers of Tibrena Sibolangit. Questionnaires were distributed to tourists who had visited Tibrena Sibolangit and observations and interviews were carried out directly with the manager. Based on the results of this study, the tourist attraction owned by Tibrena Sibolangit is an artificial tourist attraction. Therefore, the researcher hopes that through this research it can be used as evaluation material to increase the tourist attractiveness that is owned.